Microencapsulation of citronella oil with carboxymethylated tamarind gum - Keonakhone Khounvilay (2018)
Tamarind gum (TG) and carboxymethylated tamarind gum (CTG) were used as wall material to prepare citronella oil microcapsules by spray-drying. The aim of this work was to study the effect of wall-to-core ratio and fluid viscosity on emulsion droplet and microcapsule size, in order to maximize encapsulation efficiency (EE). EE was directly influenced by gum-to-oil ratio variations. Results showed that emulsion droplet size (D32) of CTG ranged between 0.18 to1.31 µm, smaller than those obtained for TG, which ranged from 0.87 to 2.91 µm. CTG microcapsules had a smooth surface and a spherical shape, as observed by scanning electron microscopy (SEM). Surface oil content and total oil content affected encapsulation efficiency. TG microcapsules showed lower EE than CTG microcapsules, which was related to the viscosity of gum to oil ratio. The maximum EE occurred at 1.14 gum to oil ratio for CTG microcapsules (87 %). (c) 2018, Walailak University.